METODOLOGIA PARA OBTENÇÃO DE IMAGENS DE ÁCIDO HÚMICO POR MEIO DA TÉCNICA DE MICROSCOPIA DE FORÇA ATÔMICA - Ales, Rosana (2014)
The technique of atomic force microscopy (AFM) has been one of the most used techniques to elucidate and characterize the structural models of Humic Substances (HS). Although this technique has been employed in the analysis of SH, there is not in the literature a standardized methodology of preparation of samples for analysis by AFM. The soil organic matter (SOM), which comes from its solid phase, can be divided into humic and not humic substances. The last one is usually constituted by humic acid (HA), fulvic acid (FA) and humin (UH). There are several structural proposals for humic substances, but none is entirely satisfactory because they consist of a heterogeneous mixture of functional groups and chemical characteristics are not defined, showing lack of genetic structural identity. The search for a structure or structural models for SH is one of the most controversial topics in the field of Soil Science. Due to different approaches, the current research aimed to test and propose methodological procedures to obtain images of humic acid (one of the fractions of humic substances) in soil by Atomic Force Microscopy. The soil in which the humic acid was extracted by chemical fractionation process is from a floodplain area, cultivated, located in the Experimental Station of the Agronomic Institute of Paraná in the city of Ponta Grossa – PR, with depth collection of 0 - 10 cm. Several methodological procedures were performed to obtain samples of HA, both in conventional procedure (stirring) of the solution and using the ultrasound to dissolve the humic acid. The two methodologies for sample preparation are valid to obtain images of HA through the AFM, however, with the use of ultrasound, samples were prepared in a shorter period.